Hak atas pendidikan sebagai hak konstitusional dalam sistem pendidikan indonesia dan finlandia - Roihan Luthfi Daulay; Ahmad Fauzi Harahap; Surya Hakiki; Roy Candra; Lysa Angrayni (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2026)
Abstract The right to education is a fundamental human right guaranteed by international legal instruments and the constitution of every state. This article discusses the right to education as a constitutional right within the educational systems of Indonesia and Finland through a normative legal approach using comparative study methods. The purpose of this research is to analyze the regulation of the right to education in the constitution, educational policies, and their implementation in both countries. Indonesia places the right to education within the 1945 Constitution of the Republic of Indonesia, particularly Article 31, which emphasizes the state’s obligation to provide education for all citizens. Meanwhile, Finland is recognized as one of the countries with the best education systems in the world, ensuring free education, equal access, and high-quality education as a manifestation of human rights fulfillment. The results of this study indicate that although Indonesia has constitutionally guaranteed the right to education, its implementation still faces various challenges, such as inequality in educational access, disparities in teacher quality, and uneven educational facilities. In contrast, Finland has successfully implemented the right to education effectively through educational policies that prioritize equality, student welfare, and teacher professionalism. This comparison demonstrates that the fulfillment of the right to education depends not only on constitutional regulation but also on the state’s commitment to implementing fair and inclusive educational policies.